The Development of Customer Loyalty Model for Mobile Travel Agent Application - Budhi Prihartono; Muhammad Azhar Ashari; Aldila Rizkiana (Department Industrial Engineering, University of Muhammadiyah Malang, 2020)
The growth of smartphone users in Indonesia opens up business opportunities for service providers, particularly via m-commerce. However, along with these great opportunities and rivalry, service providers are required to make consumers faithful to the products and services they deliver. This research aims to develop a conceptual model for an application based on m-commerce, particularly mobile travel agent applications. The research model is based on applying five dimensions of Mobile Service Quality (M-S-QUAL), customer engagement, and commitment as the predecessor factors of customer loyalty. The study was conducted on 760 MTA application users who participated in an online survey. The data were divided into two groups based on income level to be further analyzed using the Multigroup Structural Equation Modeling (SEM). The Multigroup SEM analysis shows that the concept of customer loyalty was explained differently by the two groups with different income levels.